Promoção e avaliação da atitude de Vigilância Nutricional na Atenção Básica à Saúde de municípios das bacias Piracicaba-Capivari - Camargo, Andreza Alves; Oliveira, Maria Rita Marques de [UNESP]; Renosto, Rosele Valota; Vieira, Carla Maria (My University, 2010)
Considering the importance of food and nutritional surveillance as part of a community's basic health care, our objective was to expose and discuss the educational experience of eleven municipalities of the state of São Paulo geared to build an attitude of nutritional security. The accounts were made in the form of workshops with the contribution of basic health care workers of each municipality, based on daily field worksheets and followed by an evaluation process, which used a semi-structured questionnaire. The results were classified into four categories. The methodology, based on the actual participation in the workshops was considered adequate, although some exposure and removal of personal inhibitions were necessary. These barriers were left behind with the aid of group dynamic exercises. Among the themes treated, anthropometry was highlighted because of insufficient technical know-how and standardization. An attitude towards nutritional surveillance was recognized by the health-care professionals as an important basis for the nutritional practice in order to attain food and nutritional security.

Considerando a importância das ações de alimentação e nutrição na Atenção Básica à Saúde para a Segurança Alimentar e Nutricional da população, o objetivo foi apresentar e discutir uma experiência educativa de promoção da atitude de vigilância nutricional, desenvolvida em oficinas com trabalhadores da atenção básica de onze municípios do interior paulista. Trata-se de um relato de experiência que constou da realização e observação de oficinas com registro em diário de campo, seguidas de processo avaliativo, a partir de questionários semi-estruturados, com profissionais das equipes de atenção básica dos municípios. Os resultados foram organizados e analisados sob a forma de quatro categorias. A metodologia participativa e vivencial das oficinas foi considerada adequada, porém demandou acolhimento dos sentimentos revelados pelos participantes, tais como constrangimento e inibição, superados após o desenvolvimento de dinâmicas de grupo. Dentre os temas trabalhados a antropometria teve destaque, indicando a falta de padronização e conhecimento técnico. A atitude de vigilância nutricional foi reconhecida pelos profissionais de saúde como importante para lhes dar respaldo nas práticas específicas de nutrição, contribuindo para a segurança alimentar e nutricional da população.
Promotion and evaluation of the Nutritional Surveillance in Primary Care of the Piracicaba-Capivari watersheds
Keywords: Public heath policies; Nutritional surveillance; Resource human qualification; Políticas públicas de saúde; Vigilância nutricional; Capacitação de recursos humanos